KUALITAS IKAN NILA DENGAN PENGAWET ALAMI EKSTRAK DAUN POSLEN DAN VARIASI LAMA PERENDAMAN - Alvia Quronita Ayuninisai Sholihah (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2023)
Tilapia is a freshwater fish that is very popular with the public because it has thick meat, savory taste, is easy to cultivate, and has a fairly high nutritional content. Per 100g of tilapia meat contains 16.79g of protein, 0.18g of fat, and 0.32g of carbohydrates. The decrease in the quality of tilapia often occurs due to the activity of microorganisms, so preservation is needed. Active compounds in poslen leaves such as alkaloids, flavonoids, terpenoids, sterols, phenols, saponins, and tannins can be used as inhibitors of the decay process by microorganisms. The purpose of this study was to determine the quality (protein content, moisture content, pH, and sensory) of tilapia with natural preservatives poslen leaf extract and variations in immersion time. This research method used a completely randomized design (CRD) with 2 factors. Factor 1was the concentration of poslen leaf extract 50%, 60%, and 70%, and factor 2 was soaking time for 60 minutes and 90 minutes. The best results showed that the L1P3 treatment (70ml of poslen leaf extract + 100ml of distilled water with a soaking time of 60 minutes) with a protein content of 22.37%, water content 76.83%, and pH 6 with a fresh aroma and specific smell, prominent and bright eyeballs, bright color and less light, dense and elastic texture, and bright red gills and without mucus. The shelf life of tilapia in each treatment at room temperature after 5 shows the results are not suitable for consumption.